CLINICAL PROFILE OF CHILDREN REFRACTIVE ERRORS IN A SECONDARY HEALTH CARE HOSPITAL OF BEKASI WEST JAVA: Oral Presentation - Observational Study - Ophthalmologist - LASMIDA RUTH A SIMATUPANG (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : The aim of this study was to study the pattern of refractive errors and its association among children visited Hermina Hospital Bekasi. Methods : A hospital based retrospective review was conducted on children visiting Ophthalmology Outpatient Clinic of Hermina Hospital Bekasi from October 2022 to February 2023. Results : A total of 104 children (208 eyes) aged 5-18 years were diagnosed with refractive errors. Mean age of presentation was 11.13±3.38 years with male to female ratio of 1:1.6. At the time of presentation, 50% children suffered from mild moderate visual impairment. Most of the children have mild (≤3.00D) refractive error (70.2%) with spherical equivalents ranged from +4.50 D to -10.00 D. Astigmatism was found in 166 eyes (79.8.%) followed by myopia (39;18.8%) and hypermetropia (3; 11.78%). Compound myopic astigmatism was the commonest type of astigmatism (131;79.4%). With regards to the age categories, 23.9% of the children aged 10-14 years had myopic spherical equivalents, compared with 13.1% of children between 5 and 9 years old. Conclusion : Refractive errors was a common diagnosis among children seen in our secondary health care hospital. Most of the children with refractive errors present with mild to moderate decrease in visual acuity and had benefited from an optical correction by glasses.